2016
DOI: 10.1074/jbc.m116.717652
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Proteasome Activity Induces Formation of Alternative Proteasome Complexes

Abstract: The proteasome is an intracellular protease complex consisting of the 20S catalytic core and its associated regulators, including the 19S complex, PA28␣␤, PA28␥, PA200, and PI31. Inhibition of the proteasome induces autoregulatory de novo formation of 20S and 26S proteasome complexes. Formation of alternative proteasome complexes, however, has not been investigated so far. We here show that catalytic proteasome inhibition results in fast recruitment of PA28␥ and PA200 to 20S and 26S proteasomes within 2-6 h. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
56
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 69 publications
9
56
0
Order By: Relevance
“…Although PA28γ interacts with the 20S proteasome, we identified only the α6 subunit (PSMA1) in the conditions used. However, we found all subunits with high H/L ratios when PA28γ pulldowns were performed in the presence of proteasome inhibitors (data not shown), confirming that PA28γ/20S proteasome interaction is labile (31) and is stabilized upon proteasome inhibition (11,43).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Although PA28γ interacts with the 20S proteasome, we identified only the α6 subunit (PSMA1) in the conditions used. However, we found all subunits with high H/L ratios when PA28γ pulldowns were performed in the presence of proteasome inhibitors (data not shown), confirming that PA28γ/20S proteasome interaction is labile (31) and is stabilized upon proteasome inhibition (11,43).…”
Section: Discussionmentioning
confidence: 53%
“…However, they are also found in hybrid proteasomes, i.e. 20S proteasome bound to a PA28 heptamer on one end and a 19S complex on the other end (11) and are thus likely to also participate in ATPdependent degradation of ubiquitylated proteins.…”
Section: Introductionmentioning
confidence: 99%
“…The 20S may associate with other activators/inhibitors, such as the proteasome activator PA200 or the proteasome regulator PI31, forming alternative proteasome complexes with different functions and substrate specificities. While PA200 works in an ubiquitin-and ATP-independent manner unless in complex with 20S and 19S, the function of PI31 is still not well characterized (Fort et al, 2015;Welk et al, 2016). Interestingly, seed storage proteins, which are abundant in dry seeds and are degraded during germination to sustain seedling growth, are the major forms of carbonylated (oxidized) proteins and thus likely degraded by the 20S during germination (Job et al, 2005).…”
Section: Aba Inhibits Seed Germination At 32°c Through Downregulationmentioning
confidence: 99%
“…REGγ is important for responses to genotoxic and oxidative stress as well as the impairment of proteasome function, which is for example the case in neurodegenerative diseases (25). Interestingly, it was shown that cellular REGγ is massively recruited to proteasomes after non-toxic treatment with proteasome inhibitors (26). Furthermore, recently, a specific interactor of REGγ has been identified, also called PIP30, which positively modulates the interaction of REGγ to the 20S proteasome complex and alters the selectivity of the REGγ/20S proteasome complex towards different peptides (27).…”
Section: Introductionmentioning
confidence: 99%